The Effect of Work Motivation, Communication and Work Environment on Employee Performance at the Binjai Pratama Tax Service Office - Hutasuhut, Ernawati; Gultom, Liana Meliati; Daulay, Hatta; Pulungan, Syaripuddin; Isnaini, Dewi Budiarti; Tarigan, Nur M. Ridha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of work motivation, communication and work environment partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Binjai. with a population of 82 people, and a study sample. of 80 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained work motivation have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Binjai, this is supported by the results of t count analysis > t-table (2,639 > 1,992) at n = 80 at 95% significance level.